Identification of risk factors in pre-term infants with abnormal general movements - Domagalska-Szopa, Małgorzata; Szopa, Andrzej; Serrano-Gómez, María Eugenia; Hagner-Derengowska, Magdalena; Behrendt, Jakub (Frontiers in Neurology, 2022)
IIntroduction. This study aimed to investigate the relationship between prenatal, perinatal and postnatal risk factors of neurodevelopmental impairment with the outcomes of General Movement Assessment in preterm born infants at 3-5 months. We wanted to identify the risk factors associated with predictors of psychomotor development in preterm newborns i.e. normal Fidgety Movements, absent Fidgety Movements, or Abnormal Fidgety Movements, assessed during the fidgety period of motor development. Method. The risk factors for the development of neuromotor deficits in 164 pre-term infants with a high risk of developing, who were qualified for the SYNAGIS programme (prophylactic of Respiratory Syncytial Virus Infection) were analysed. Based on the General Movements Assessment, all participants were divided into three group of infants who presented: normal Fidgety Movements; 2) absent Fidgety Movements; 3) abnormal Fidgety Movements. Results. The results of current study suggest that abnormal general movements are not only associated with commonly known factors like birth asphyxia, respiratory distress syndrome, periventricular leukomalacia, intraventricular hemorrhage grade 3-4 but also predict the development of motor impairments. In the present study, several specific risk factors including bronchopulmonary dysplasia, infertility treatments, maternal acute viral/bacterial infections during pregnancy, and elevated bilirubin levels were identified as attributes of the atypical fidgety movement pattern. Conclusions. Additional clinical data such as risk factors of Neurodevelopmental impairment associated with the early predictors of psychomotor development in preterm newborns, i.e. absent Fidgety Movements, or abnormal Fidgety Movements may be helpful to predicting neurological outcomes in preterm infants with developmental concerns at first months of life.